Aromaterapi Lavender dalam Menurunkan Tingkat Kecemasan Pasien Pre Operasi Sectio Caesarea - Sri Devi; Tutik Agustini; Yusrah Taqiyah (Window of Nursing Journal, 2023)
Anxiety is an unpleasant feeling described by restlessness or tension and abnormal hemodynamic signs. Anxiety in sectio caesarea patients can be reduced by pharmacological and non-pharmacological therapy. This study aims to determine the effect of giving aromatherapy to preoperative patients on reducing anxiety levels at RSIA Kadijah 1 Muhammadiyah Makassar. The design used is a quantitative method with a quasi-experimental pre-post test design without control. The patient population was obtained as many as 138 patients with a sampling technique using the Slovin formula with an error rate (margin of error) of 10%, so the number of samples was 58 respondents. The instrument used in data collection is the HARS scale questionnaire. The results of the study The highest patient anxiety level before giving lavender aromatherapy experienced a mild level of anxiety with a score of 14-20 as many as 42 people or 72.4%, after being given lavender aromatherapy the highest patient anxiety level experienced a non-anxious anxiety level with a score of <14 as many as 28 people or 48.3% with the results of the paired t-test statistic obtained the value of = 0.001 where the level of significance (ρ <0.05). The conclusion of this study is that there is an effect of lavender aromatherapy on reducing anxiety levels in preoperative sectio caesarea patients.